Objective evaluation of volumetric changes during breast augmentation using intraoperative three-dimensional surface imaging. Issue 9 (September 2022) - Koban, K.C.; Li, Z.; Etzel, L.; Schenck, T.L.; Härtnagl, F.; Giunta, R.E.
Summary: Background: Breast volume estimation and implant size are crucial factors to achieve a symmetrical result in esthetic and reconstructive breast surgery. Although three-dimensional surface imaging (3DSI) has allowed for a better understanding of breast shape, size, and asymmetry during patient consultation, its use has been limited regarding intraoperative decision-making. Objective: To validate the intraoperative use of a portable hand-held 3D surface imaging device as an objective tool to assess volumetric changes during breast augmentation surgery. Methods: Patients receiving bilateral, submuscular breast augmentation were enrolled for this study. Intraoperative 3DSI was conducted using the Sense 3D scanner, allowing for digitalization of the operating field. Intraoperatively gauged volume changes caused by known implant volumes were compared with digital measurements calculated from 3D surface images of the operating field. Digital intraoperative breast volumes were compared to the pre- and postoperative Vectra XT reference system. Results: Eighty individual breasts of 40 patients were successfully 3D imaged before incision and after wound closure. There was no significant difference between digital breast volumes by intraoperative and outpatient 3DSI. Intraoperative pre- to postoperative 3D breast volume change showed no significant difference to the known implant volume ( p = 0.124, mean deviation of 5.8 ± 24.3 mL and 2.0 ± 9.0%). Conclusions: Our findings showed a high correlation regarding intraoperative digital breast volumetric changes. Intraoperative use of 3DSI yielded objective data during breast augmentation. This novel technique could beneficially impact future breast implant selection, especially in cases with breast asymmetry and the need for differently sized implants.